Impact on Some Soil Physical and Chemical Properties Caused by Metal and Metallic Oxide Engineered Nanoparticles: A Review - Arancibia-Miranda, N; Arancibia-Miranda, N (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In recent years, the release of metal and metallic oxide engineered nanoparticles (ENPs) into the environment has generated an increase in their accumulation in agricultural soils, which is a serious risk to the ecosystem and soil health. Here, we show the impact of ENPs on the physical and chemical properties of soils. A literature search was performed in the Scopus database using the keywords ENPs, plus soil physical properties or soil chemical properties, and elements availability. In general, we found that the presence of metal and metallic oxide ENPs in soils can increase hydraulic conductivity and soil porosity and reduce the distance between soil particles, as well as causing a variation in pH, cation exchange capacity (CEC), electrical conductivity (EC), redox potential (Eh), and soil organic matter (SOM) content. Furthermore, ENPs or the metal cations released from them in soils can interact with nutrients like phosphorus (P) forming complexes or precipitates, decreasing their bioavailability in the soil solution. The results depend on the soil properties and the doses, exposure duration, concentrations, and type of ENPs. Therefore, we suggest that particular attention should be paid to every kind of metal and metallic oxide ENPs deposited into the soil. © 2023 by the authors.